2002
DOI: 10.1001/archpsyc.59.10.921
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Interventions Designed to Reduce the Risk of Progression to First-Episode Psychosis in a Clinical Sample With Subthreshold Symptoms

Abstract: More specific pharmacotherapy and psychotherapy reduces the risk of early transition to psychosis in young people at ultra-high risk, although their relative contributions could not be determined. This represents at least delay in onset (prevalence reduction), and possibly some reduction in incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
673
1
32

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 929 publications
(723 citation statements)
references
References 37 publications
17
673
1
32
Order By: Relevance
“…Thus far, one randomized clinical trial (RCT) has demonstrated the superiority of low dose risperidone in combination with cognitive behavioral therapy over "needs-based intervention," with a significant difference in rates of transition to psychosis (9.7% vs. 35.7%) and reported low incidence of side effects and little stigma (McGorry et al, 2002). Another RCT, which was placebo-controlled and double-blind, had differential rates of conversion to psychosis at 1 year (placebo 34.5% vs. olanzapine 16.1%) that was not statistically significant, probably due to low power ; unfortunately, weight gain was also much higher in the olanzapine group (8.8 vs. 0.3 kg).…”
Section: Defining the At-risk Populationmentioning
confidence: 99%
“…Thus far, one randomized clinical trial (RCT) has demonstrated the superiority of low dose risperidone in combination with cognitive behavioral therapy over "needs-based intervention," with a significant difference in rates of transition to psychosis (9.7% vs. 35.7%) and reported low incidence of side effects and little stigma (McGorry et al, 2002). Another RCT, which was placebo-controlled and double-blind, had differential rates of conversion to psychosis at 1 year (placebo 34.5% vs. olanzapine 16.1%) that was not statistically significant, probably due to low power ; unfortunately, weight gain was also much higher in the olanzapine group (8.8 vs. 0.3 kg).…”
Section: Defining the At-risk Populationmentioning
confidence: 99%
“…The basis of the vulnerability to psychosis in this group is unknown and, whilst evidence shows that psychological and pharmacological interventions improve outcomes (Bechdolf et al, 2005;McGorry et al, 2002;Miller et al, 2003;Phillips et al, 2005;Ruhrmann et al, 2005;Woods et al, 2003), treating high risk subjects remains controversial since most of them are not destined to develop the disease (Broome et al, 2005b;Cornblatt et al, 2001;Haroun et al, 2006). The identification of biological measures associated with a subsequent transition to psychosis would help to target early treatment to those who require it (Bender et al, 2007;Eastvold et al, 2007;Mason et al, 2004;Pantelis et al, 2003;Simon et al, 2007;van der Stelt and Belger, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…6 Another controlled study examined the effects of risperidone treatment on the progression of "ultra high risk" individuals defined as those with nonspecific symptoms, impaired functioning, and a first-degree relative with psychosis; attenuated positive psychotic symptoms lasting at least a week; or brief episodes of psychotic symptoms not sustained beyond a week. 7 Significantly fewer individuals went on to develop a first-episode psychosis in the group treated with risperidone.…”
Section: Treatment Of Prodromal Symptomsmentioning
confidence: 99%
“…[3][4][5][6][7] A "prodrome" of depression, decreased concentration and attention span, lack of motivation, apathy, and social withdrawal can precede the first psychotic symptoms in schizophrenia by as much as 4 or 5 years. 2,9,10 Some patients never progress beyond this phase of the illness.…”
Section: Treatment Of Prodromal Symptomsmentioning
confidence: 99%
See 1 more Smart Citation